Labor force participation of rural women and the household's nutrition: Panel data evidence from SAT India. (July 2021) - Sangwan, Nikita; Kumar, Shalander
Highlights: This paper investigates the effect of rural women labour force participation on the households' dietary diversity. We find a significant improvement in dietary diversity with increased women labour force participation. There exists significant heterogeneity in the effect between paid and unpaid work-days. Empowerment due to labour force participation drives the results for paid work and the self-consumption of home-produced goods for the unpaid work. No deleterious effects on the health indicators of women despite increased time burden. Abstract: This paper investigates the role of women's labor force participation in the household's dietary diversity and the value of home-production. Using unique household panel data from Semi-Arid tropics of India, empirical estimations from a household fixed effects model reveal a positive significant effect of workdays of women on dietary diversity (overall and home-produced) and home-production. Our findings highlight a significant heterogeneity in the effect by type of work—paid and unpaid. The results for paid work are driven by a greater decision-making power emanating from labor force participation of women. Unpaid work, on the other hand, operates through the self-consumption of home-produced goods. We show that correcting for endogenous labor force participation of women leaves our conclusions unchanged. The results suggest that interventions boosting female labor force participation in paid activities are nutrition enhancing for the household and work towards improving women's bargaining power within the household. Moreover, we rule out deleterious effects on health indicators of women despite increased time burden.